Cycling tour planning challenges by operators - Silva, Natalya Reis da; Oliveira, Rodrigo Ribeiro de (Brazilian Journal of Production Engineering, 2022)
The trend for the search of ecological activities and new experiences places bike trips, which have the bicycle as the main means of transportation, as an alternative for the practice of leisure. The experience offered to consumers in the market, including tourists, is the result of an efficient planning of the service provision process, which should also be observed by operators when producing and offering trips. Thus, this work aimed to analyze the challenges faced in the operation of the supply of adventure tourism services of bicycle tours with support, based on the Tourism System (SISTUR). To this end, an exploratory and descriptive research was carried out, data collection occurred through bibliographic and documentary research and multiple case studies with three tour operators located in the city of São Paulo. The three operators were interviewed via e-mail and Whatsapp and the answers showed the different natures that make up the operational challenges faced by these operators, being the articulation of the elements for the provision of cycle tours with support, the poor infrastructure of the host cities, the transportation of the bicycle and the inflexibility in the supply of accommodation services for specific cycle tours.
Keywords: Adventure tourism; supported cycling; adventure tourism operators; operation; public policy